To be or not to be: navigating the influence of MicroRNAs on cervical cancer cell death - Mohammad Taghizadieh; Masoumeh Kalantari; Roksana Bakhshali; Sepehr Kobravi; Shayan Khalilollah; Hossein Bannazadeh Baghi; Mobina Bayat; Javid Sadri Nahand; Reza Akhavan-Sigari (Cancer Cell International)
Abstract With all diagnostic and therapeutic advances, such as surgery, radiation- and chemo-therapy, cervical cancer (CC) is still ranked fourth among the most frequent cancers in women globally. New biomarkers and therapeutic targets are warranted to be discovered for the early detection, treatment, and prognosis of CC. As component of the non-coding RNA’s family, microRNAs (miRNAs) participate in several cellular functions such as cell proliferation, gene expression, many signaling cascades, apoptosis, angiogenesis, etc. MiRNAs can suppress or induce programmed cell death (PCD) pathways by altering their regulatory genes. Besides, abnormal expression of miRNAs weakens or promotes various signaling pathways associated with PCD, resulting in the development of human diseases such as CC. For that reason, understanding the effects that miRNAs exert on the various modes of tumor PCD, and evaluating the potential of miRNAs to serve as targets for induction of cell death and reappearance of chemotherapy. The current study aims to define the effect that miRNAs exert on cell apoptosis, autophagy, pyroptosis, ferroptosis, and anoikis in cervical cancer to investigate possible targets for cervical cancer therapy. Manipulating the PCD pathways by miRNAs could be considered a primary therapeutic strategy for cervical cancer.